ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PADA PUSAT PELAYANAN SATU ATAP (PPSA) PT. PELABUHAN INDONESIA II (PERSERO) CABANG PANJANG - Department, administratio; Andhiny, Maya Shella; Mulyana, Nana; Reza, Izzul Fatchu (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. This study aims to determine and analyze the factors that affect the quality of serviceat One Stop Service Center (PPSA) in PT. Pelabuhan Indonesia II (Persero) Panjang Branch of BandarLampung City. The method used is qualitative with descriptive type. Determination of informantsbased on the criteria of informants obtained through snowball sampling technique. Furthermore,data collection techniques used are in-depth interviews documentation and observation. While thedata analysis techniques used are data reduction, data presentation, conclusion, and verification.The results showed that the factors that influence or encourage the quality of service at One StopService Center (PPSA) in PT. Pelabuhan Indonesia II (Persero) Panjang Branch of Bandar Lampung Cityinclude human resources, services through customer-oriented system, facilities dan infrastructure,and programme activities by engaging customers. While the inhibiting factor of service quality atPPSA is caused the internal factor a company, covering system or network coming from networkprovider itself. Keywords: Service Quality, Management, and Human Resources